Proposition From The "Quote" Of Muhammad Ali. - Jaisy Alfaliq Tisara; Tatan Tawami (Jurnal Pendidikan dan Sastra Inggris, 2023)
This study analyzes the propositions presented in Muhammad Ali's quotes shared on his Facebook account on February 12, 2013. These quotes become the main data, accompanied by Larson's theory of propositions as supporting data. the method used in this research is descriptive qualitative. This study aims to reveal the meaning of the quote from Muhammad Ali. This method prioritizes broad understanding and solid explanations. By looking closely at these quotes, this research improves our understanding of the underlying meaning of Muhammad Ali's words. Through an analysis based on real objects. this study analyzes the overall content, context, and potential implications, which will reveal the meaning that is in this quote from Muhammad Ali.By analyzing the meaning and context in the quotations from Muhammad Ali, this study seeks to explore and reveal what Muhammad Ali meant to convey. This helps us gain greater insight into the true intent underlying the statement..